London 1900 : the imperial metropolis - Schneer, Jonathan (New Haven : Yale University Press, 1999)
"London in 1900 was the greatest city on earth - the capital of an empire on which the sun never set. This book is the first to examine this powerful and influential city at the turn of the century and to invesitgate its relationship with Britain's far-flung empire."--Jacket.
London in 1900 -- Imperial London -- The face of imperial London -- The nexus of empire -- The city -- Popular culture in the imperial metropolis -- Alternative imperial Londons -- Limning female gender boundaries -- London's radical and Celtic fringe -- Dadabhai Naoroji and the search for respect -- Roots of the Pan-African Conference -- The Khaki election of 1900.
Includes bibliographical references (pages 307-321) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: London (England) -- History -- 1800-1950.; Imperialism -- Public opinion -- History; Nineteen hundred, A.D.; London (England) -- History -- 19th century; London (England) -- Social conditions -- 19th century; London (England) -- Politics and government -- 19th century; Londres (Angleterre) -- Histoire -- 1800-1950.; Impérialisme -- Opinion publique -- Histoire; Mil neuf cent; HISTORY; Imperialism -- Public opinion; Nineteen hundred, A.D.; England -- London; Imperialismus; Großbritannien; London; Britse Gemenebest; Cultuurgeschiedenis; Londen; Great Britain; Regions & Countries - Europe; History & Archaeology; 1800-1950; History